Enhancing human rights: computer and information technologies with access for all. (1st January 2012) - Barile, Maria; Fichten, Catherine S.; Asuncion, Jennison V.
Inclusion of people with disabilities in the new knowledge-based society can be facilitated by universal design of information and communication technologies (ICTs). This will be a first step in providing the tools to reduce poverty and enhance human rights. Here, we present highlights of the Adaptech Research Network's ten-year corpus of empirical work on education and ICTs for postsecondary learners with disabilities. Consistent with various versions of the social model of disability, recurring findings from our research link the need for availability, affordability and accessibility of both the technological and learning environments and show a clear link to the notions advocated by various versions of the social model of disability. When these three pertinent elements are provided, individuals with disabilities achieve academic success – and obtain jobs – at the same rate as their non-disabled peers.